An Approach For Selecting CO2 Removal Technology In Indonesia's Upstream Natural Gas Industry Using AHP Method - Nugroho, Agung Azan; Azis, Muhammad Mufti; Ariyanto, Teguh (Tamkang University, 2023)
Impurities are commonly found in natural gas which is produced from reservoirs deposit. The predominant impurities come in CO2 forms. Hence, the selection of proper CO2 removal technologies is a significant step in process engineering as it strongly affects the size of CAPEX and OPEX. However, the selection of the CO2 removal process is not always trivial and further it must be conducted in the beginning of the project feasibility study. Currently, there are several CO2 removal technologies including absorption, adsorption and membranes. Considering their advantages and limitations, there is a need to analyse the relationship between the CO2 removal cost with the required product gas, impurities, flow capacity, geographical factor and CO2 tax in Indonesia. Thus, these criteria are evaluated through the multi-criteria decision-making (MCDM) technique for selecting the most suitable technology for removing CO2. In this study, Analytic Hierarchy Process (AHP) is chosen and applied to evaluate the significance of each criterion. The results showed that absorption using the amine system is frequently used in Indonesia's upstream natural gas industry. Furthermore, the use of the adsorption method (pressure swing adsorption) for a low-quantity gas feed also showed good results. The use of AHP method for selecting CO2 removal technology in Indonesia's upstream natural gas industry can be used by investors and policymakers as a useful pre-investment tool analysis in developing new fields. The current proposed method aims to screen the best CO2 removal technology by taking into accounts technical performance, revenue and cost, as well as reducing emissions.